Therapeutic potential of the probiotic Lactiplantibacillus plantarum BX 62 and its postbiotics in alleviating rheumatoid arthritis in mice - Qi Qin; Gang Hu; Xiaoni Zhou; Ruizhe Zhu; Jianying Chen; Kangtai Zeng; Jingwu Wu; Jing Wei; Tingtao Chen; Xusheng Guo (Current Research in Food Science)
This study comprehensively investigated the probiotic potential of Lactiplantibacillus plantarum and its derived postbiotics in alleviating rheumatoid arthritis (RA) symptoms in mice. In vitro analyses established the probiotic characteristics of L. plantarum, highlighting its acid tolerance, bile salt resistance, and adhesion abilities. Subsequent in vivo experiments demonstrated that administering live L. plantarum significantly reduced arthritis scores, paw oedema, and intestinal permeability in RA mice, indicating its therapeutic potential. Furthermore, the study explored the effects of L. plantarum-derived postbiotics, including both the cellular remnants and supernatant, on RA. Notably, both the inactivated body of L. plantarum and its supernatant effectively reduced osteoarthritic damage, intestinal pathological changes, autoantibody levels, cytokine imbalances, and oxidative stress in RA mice. Additionally, qPCR analysis revealed that L. plantarum interventions restored gut microbiota composition towards a healthier profile, resembling that of normal mice. Collectively, these findings underscore the therapeutic benefits of L. plantarum and its postbiotics in ameliorating RA symptoms, emphasising their potential as novel therapeutic agents for managing RA.